OP49 Development of a theory-based implementation intervention to increase uptake of diabetic retinopathy screening. (3rd September 2019) - Riordan, F; Racine, E; Smith, S; Murphy, A; Browne, J; Kearney, P; McHugh, S
Abstract : Background: Diabetic retinopathy is a common complication of diabetes affecting the blood vessels at the back of the eye. Despite evidence that diabetic retinopathy screening (DRS) is effective, uptake continues to be sub-optimal in many countries, including Ireland. As routine management of type 2 diabetes largely takes place in primary care, it is arguably the best setting in which to implement interventions to improve DRS uptake. This study aims to develop a theory-based implementation intervention to improve uptake. Methods: A four-stage systematic development process was undertaken. Target behaviours were identified through a multi-phase sequential mixed methods study involving key stakeholder interviews (n=19), and an audit of screening attendance in two primary care centres. Barriers and enablers to uptake were identified through coding interviews with patients (n=48) and health care professionals (HCP) (n=30) using the Theoretical Domains Framework (TDF). Barriers and enablers were mapped to behaviour change techniques (BCTs) to develop intervention content. The APEASE (affordability, practicability, effectiveness, acceptability, side effects and equity) criteria was used to select the components. Effectiveness was determined through a rapid evidence review. Feasibility, local relevance and acceptability of the intervention were identified through consensus group meetings with patients (n=15) and HCPs (n=16), and key stakeholder consultation, including the national DRS programme. Results: Three key behaviours were identified; one HCP-level (registration of patients for screening), and two patient-level (consent for the programme to hold their details, and attendance). Modifiable patient barriers and enablers were associated with six TDF domains. Barriers included confusion between screening and routine eye checks ('Knowledge'), forgetting ('Memory, attention, decision processes'), anticipation of a negative result ('Beliefs about consequences'). Enablers included a recommendation from friends/family or HCPs ('Social Influences'), recognising the importance of screening for early detection ('Beliefs about consequences'), ownership over their condition ('Identity'), and being in a routine of attending tests ('Beliefs about capabilities'). HCP barriers included the time to register patients which was impeded or supported by practice resources ('Environmental context and resources'), and a lack information on screening uptake in their local area ('Knowledge'). Following the consensus meetings, consultation and evidence review, ten BCTs were included and operationalised as an implementation intervention targeting professionals (reimbursement, training, audit/feedback and electronic prompt) and patients (face-to-face/phone reminder messages, GP-endorsed reminder letter and information leaflet). Conclusion: A multi-stage process combining theory, consultation of multiple stakeholders and existing evidence, was used to develop a multifaceted implementation intervention, targeting both professional and patients, to increase uptake of DRS. The feasibility of delivering the intervention in primary care will be evaluated through a pilot trial.